Changes of groundwater quality in sulphide-bearing mine-tailings as a result of remediation at Kristineberg, northern Sweden - Alakangas, Lena; Lundberg, Angela; Öhlander, Björn (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2007)
At the Kristineberg mine in northern Sweden, sulphide-rich tailings left open for 50 years were remediated in 1996 by applying double dry cover on one part of an impoundment, and raised groundwater level combined with simple till cover on the other part. Groundwater pipes installed in the impoundment were sampled from 1998 during a period of 6 years. The results showed that the groundwater quality varied considerably in the impoundment, even under the same type of cover. Secondarily retained Fe, S, Mg, Mn and Z were remobilised when the groundwater was raised. In the part with raised groundwater level, the average concentration of Fe ranged from 2700 to 9000mg/l in 1998, and the range for S was 2200 to 7000mg/l. During 2003 the average concentrations had decreased and ranged between 150 and 900 mg/l for Fe and between 130 and 900 mg/l for S. The improvement of the water quality was caused by inflow of less contaminated groundwater and decreasing sulphide oxidation rate. The redox potential generally decreased and pH increased. The concentrations of Cd, Cu and Pb in groundwater decreased rather rapidly all over the impoundment after remediation. In areas with relatively high pH and low redox potential, Al, Cd, Co, Cr, Cu, Fe, Ni, Pb and Zn were almost depleted. Godkänd; 2007; Bibliografisk uppgift: CD; 20071207 (mivu)